The Legal Settlement Aspects of Land Grant Disputes Where Buildings Have Been Erected Due to Weak Evidence - Satyo, Bagus Khusfi; Hafidz, Jawade (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2023)
An agreement can be made if there is a skill, a halal cause, a thing and an agreement between the two parties. This research is descriptive analytical research which attempts to describe systematically and carefully the facts about the characteristics of a certain population. The approach that this author will take is the Sociological Juridical approach. The Sociological Juridical Approach emphasizes research that aims to obtain legal knowledge empirically by going directly into the object. Sociological Juridical Research is legal research using secondary data as initial data, which is then continued with primary data in the field. or towards society, researching the effectiveness of a Ministerial Regulation and research that wants to find relationships (correlations) between various symptoms or variables, as data collection tools consisting of document or library material studies and interviews (questionnaires). The Sociological Juridical Approach is aimed at reality by looking at the application of law (Das Sein). The researcher chose this type of legal research because the researcher saw a gap between the desired legal rules (Das Sollen) and the reality that occurred (Das Sein). A grant is giving something to a desired person voluntarily. In general, the definition of a gift is giving something to a desired person while they are still alive, which is different from the concept of inheritance. Grants themselves are quite often found at social events, such as giving land to social institutions or religious buildings. Not infrequently, grants are also given in the form of assets or property. Keywords: Authority; Dispute; Grant; Mediation.